Ideological Polarization through Selective Exposure: Social Media Perspectives (Sudurpaschim Spectrum, 2023)
This study seeks to outline the problems of polarization caused by social media and its current scenarios. It involves the elaboration of some important questions, but the answers are still open and cannot be overlooked. The paper discussed how social media connects people freely and how everything is done with one click. In this regard, there are many polarization effects for like-mindedness choices that have been discussed here from a social-psychological point of view. This like-minded choice can lead to an idealistic polarization, and the extremities can grow between the two polarities of disgust and hatred. Selective exposure and ideological polarization have been gradually gaining academic attention recently. This study will show that most of the research on polarization has been focused on political polarization while ideological polarization being a much broader aspect, has not been paid an equal amount of attention. Several risky indicators that pose a danger to democratic societies have been also discussed in this paper as the consequence of ideological polarization. From a socio-psychological perspective, the topic of polarization is nothing new but the issue of polarization through selective exposure in social media is on the rise. Social scientists have always serious room to explore this arena.